Analysis and Design of Web-Based Wedding Planner Applications Case Studies on Resta Wedding Organizers - Dennis Gunadi; Riki (bit-Tech, 2022)
Wedding Planner is a service that serves to assist the bride and groom in doing a planning and implementation of the entire event in a wedding party by adjusting all the needs and desires of the bride and groom so as to make the desired wedding party. Problems that occur Data management and Marketing Services wedding organizer in Resta Wedding Organizer is still done manually. Customers must come to the location of the wedding organizer directly to place an order, this is due to media limitations. Meanwhile wedding organizer marketing is still done through people to people, through brochures and simple social media that still impactless widespread dissemination of information. So we need other marketing media better and can reach many people.The purpose of this study is to build a Wedding Planner information system designed using web application-based information technology that has a purpose to simplify the ordering process and further expand the distribution of marketing information and sales of Wedding Planner services. Wedding Planner is using PHP programming language and MySQL as a Database and for this system development method using prototyping method which consists of the process of analysis, design, application development, evaluation and results. The Wedding Planner information system is very helpful for brides and grooms who find it difficult to plan their wedding party and want to make it easier to make reservations. With the development of technology at this time the Wedding Organizer has begun to replace the manual process into the online process with a web-based Wedding Planner information system.